Preparation of antibacterial polypropylene grafted acrylic acid and immobilized silver nanoparticles by γ-irradiation method - Viet, Dang Hoang; Xo, Duong Hoa; Luan, Le Quang (Vietnam Journal of Biotechnology, 2018)
Silver nanoparticles (AgNPs) are now being widely used as antibacterial agents due to their strong bactericidal properties and low toxicity on mammalian cells. In this study, γ-rays irradiation method was used to synthesize AgNPs from silver nitrate (AgNO3) solution and to graft acrylic acid (AAc) onto porous polypropylene (PP). Porous PP grafted with AAc (PP-g-AAc) was then immobilized with AgNPs for preparing the antimicrobial materials (PP-g-AAc/AgNPs). The results demonstrated that the grafting yield of AAc onto PP increased by the increasing of irradiation dose as well as AAc concentration. The PP-g-AAc samples with grafting degrees from 1.2 to 29.8% were immobilized with AgNPs (d 10 nm, 500 ppm) to obtain antimicrobial properties. The immobilized Ag contents were from 132 to 392 ppm and corresponded to the PP-g-AAc samples at grafting degrees from 1.2 to 29.8%. The in vitro antibacterial properties of PP-g-AAc/AgNPs materials on E. coli were evaluated and the results indicated that the bactericidal efficiency (η) increased by the increase of Ag contents in the tested materials. The germicidal activities against E. coli of PP-g-AAc/AgNPs containing 363 ppm Ag were found to be nearly 100% after treating in 30 min. In addition, the inhibition zone of this PP-g-AAc/AgNPs on E. coli was also found up to 28 mm in diameter. Thus, γ-rays radiation demonstrated a strong capability in grafting functional groups (AAc) onto porous PP. Furthermore, the porous PP grafted with AAc and immobilized with AgNPs might potentially be used for elimination of bacteria in water filtering